Introduction to Systems Analysis Mathematically Modeling Natural Systems - Imboden, Dieter M. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book builds an understanding of what systems are and how they can be described mathematically. In the context of natural science, this knowledge is of great importance. The intended audience are students in applied sciences such as earth and environmental science, geoecology, environmental chemistry and forestry. The focus is on the methods of modeling, with the aim to let readers develop models of their own as well as analyze the properties of models they encounter. Numerous practical examples from the environmental sciences illustrate the concepts, and exercises accompany each chapter. The book is written so as to be easily understandable and includes humorous cartoons. There is no derivation of mathematical formulas or technical description of modeling software. It does, however, require an understanding of calculus for the reader to apply the mathematical methods it introduces.